Impact Assessment of Technical Instruction and Vocational Andragogy Training for TVET Trainers of Bhutan - Sangay Tshewang; Yonten Pelzang; Karma Dorji (Journal of Innovation in Polytechnic Education)
This study examined the effectiveness of Technical and Vocational Andragogy or Instruction Pedagogy (ToT) training and how it can enhance trainers' performance in delivery. Trainers' performance is vital to every country; Technical and Vocational Education and Training (TVET) in Bhutan is no exception. The study was based on an explorative research design with descriptive analysis. A purposive sampling technique was used to select the respondents (trainers). The survey research instrument (self-administered questionnaire) was designed to have both open-ended and closed-ended items.